EVALUATION OF INFLIGHT ADVERTISING EFFECTIVENESS CASE STUDY: PT. ULTRA SAKTI - Rasyidah, Avi Rayhana; Aprilianty, Fitri (Journal of Business and Management, 2018)
Abstract. These days advertisers are ceaselessly searching for better approaches to communicate with their customers. Advertisers attempted to characterize and clarify customer's intention by utilizing diverse models and applying different systems for enhancing brand awareness. Unintentionally, airplane can be utilized by an advertiser to be a media of promotion, it is generally named as inflight advertising. Airasia has been using Inflight Advertising as a media for a company to advertise its product, and currently PT. ULTRA SAKTI is utilizing along AirAsia’s cabin as their media of advertisement, the products of PT ULTRA SAKTI that are promoted along the cabin side are FreshCare, MADU TJ and Hot In Cream. This paper can help advertiser to insight about inflight advertising effectiveness. Using qualitative and quantitative approach to collect the data from the passenger of AirAsia. The data were obtained from interview and surveys on AIDA Model variables with Air Asia passenger. This research found that inflight advertising has significant influence to attract attention, trigger interest, stimulate desire and urge action. This research also found that most of the respondents of passenger AirAsia still remember about this inflight advertising. In addition, the perception is showing the positive sights. Researcher then recommend the company to give more emotional shopping experience, so when the passenger has already seen the advertisement, the passenger will also see that the company gives a kind of promos, discount or something that can attract.Keywords: Inflight Advertising, AIDA Model, Perception, Indonesia AirAsia, PT. ULTRA SAKTI.